Direction‐Controlled Light‐Driven Movement of Microribbons. Issue 38 (15th August 2016) - Zhang, Yifan; Peng, Cheng; Cui, Bin; Wang, Zhengfei; Pang, Xibin; Ma, Renmin; Liu, Feng; Che, Yanke; Zhao, Jincai
Abstract : Novel direction‐controlled movements of microribbons self‐assembled from perylene diimide molecules are reported on various hydrophobic surfaces under scanning laser irradiation. A "dynamic exciton charge model" is developed to elucidate the underlying mechanism. The findings provide an innovative strategy for the design of microscale systems capable of continuous and directional movement driven by light.